The Ototoxicity of Antimalarial Drugs—A State of the Art Review - Jozefowicz-Korczynska, Magdalena; Pajor, Anna; Lucas Grzelczyk, Weronika (Frontiers in Neurology, 2021)
This review summarizes current knowledge about the occurrence of hearing and balance disorders after antimalarial drugs treatment. It also examines the clinical applications of antimalarials, their mechanisms behind this ototoxicity and how it can be monitored. It includes studies with larger numbers of patients and those in which auditory function was assessed using audiological tests. Some antimalarials have been repurposed for other conditions like autoimmune disorders, rheumatic diseases, some viral diseases and cancers. While old antimalarial drugs, such as quinoline derivatives, are known to demonstrate ototoxicity, a number of new synthetic antimalarial agents particularly artemisinin derivatives, demonstrate unknown ototoxicity. Adverse audiovestibular effects vary depending on the medication itself, its dose and route of administration, as well as the drug combination, treated disease and individual predispositions of the patient. Dizziness was commonly reported, while vestibular symptoms, hearing loss and tinnitus were observed much less frequently, and most of these symptoms were reversible. As early identification of ototoxic hearing loss is critical to introducing possible alternative treatments with less ototoxic medications, therefore monitoring systems of those drugs ototoxic side effects are much needed.